Kategoria estetyki języka w dziewiętnastowiecznym czasopiśmiennictwie dla dzieci i młodzieży = Category of language aesthetics in nineteenth century periodicals for children and adolescents - Uździcka, Marzanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of this article is to determine whether and to what extent the problem of language aesthetics was present in the nineteenth-century children`s and youth magazines, and what exponents of linguistic behavior in the evaluation of editors of press texts were considered aesthetic.
Keywords: estetyka językowa; kryterium estetyczne; kryterium narodowe; czasopismo dziecięce; czasopismo młodzieżowe; prasa; 19 w.; aesthetics of language; aesthetic criterion; national criterion; magazines for children and youth; 19th century